2019
DOI: 10.12669/pjms.35.5.1421
|View full text |Cite
|
Sign up to set email alerts
|

Strong association of anemia in people with diabetic foot ulcers (DFUs): Study from a specialist foot care center

Abstract: Background & Objective: Anemia is common finding in people with diabetes and diabetic foot ulcers. Therefore, our objective was to observe and compare the association of anemia in people with diabetic foot ulcers (DFUs) with age and sex matched people without DFUs. Methods: This prospective case control study was undertaken at a multidisciplinary diabetic foot clinic of Baqai Institute of Diabetology and Endocrinology (BIDE) between October 2014 and October 2015. Participants were categorized into tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 17 publications
3
14
0
Order By: Relevance
“…In recent studies, anemia has been demonstrated to be prevalent in patients with DM, especially in the setting of DFUs [ 39 , 40 , 41 , 42 , 43 , 44 ]. However, there are conflicting reports on the correlation between anemia and DFU prognosis.…”
Section: Pathophysiology Associated With Diabetic Wound Healingmentioning
confidence: 99%
“…In recent studies, anemia has been demonstrated to be prevalent in patients with DM, especially in the setting of DFUs [ 39 , 40 , 41 , 42 , 43 , 44 ]. However, there are conflicting reports on the correlation between anemia and DFU prognosis.…”
Section: Pathophysiology Associated With Diabetic Wound Healingmentioning
confidence: 99%
“…In anemic diabetic foot ulcers patients a poor prognosis of the ulcer healing is evident [ 21 ]. Costa et al had a similar finding where 89.6% of patients who underwent major limb amputation were anaemic, and anaemia was a significant risk factor for major limb amputation [ 20 , 24 ]. There is more evidence for a strong association between anaemia and amputation [ 21 ].…”
Section: Discussionmentioning
confidence: 91%
“…This is almost two thirds (23/31; 74.19%) of all patients who underwent major limb amputation in our study showing that anaemia was an important factor for amputation Table 3. The World Health Organization cut off point for diagnosis of anaemia is a hemoglobin level of 12.0 g/dl for females and 13.0 g/dl for males [19,20]. Diabetics have a twofold chance of developing anaemia [20][21][22][23].…”
Section: Clinical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrently, iron overload (hemochromatosis), and chronic venous disease (CVD) causes severe complication through specific organ damage in liver, heart, kidney, leg veins, and skin [ 5 ]. Diabetes, anemia, and iron deficiency are intently correlated with diabetic wound healing [ 6 , 7 , 8 ]. Diabetic wound healing is a detrimental impediment in the management of wound healing because of the pathogenic macro and microvascular complications [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%